Sustainability Matters - Virginie Servant-Miklos; Jette E. Holgaard; Anette Kolmos (Journal of Problem Based Learning in Higher Education, 2023)
The purpose of this study was to identify patterns of change in students’ awareness of, interest in and engagement with sustainability issues during the process of acclimatisation to their PBL engineering studies, and to look for differences between engineering disciplines with respect to these aspects. This study used a longitudinal qualitative approach with a theory-led thematic analysis. There were 16 participants in total, interviewed at 3 intervals during a period of 18 months at a faculty of engineering in Denmark. The authors found a pattern of increase in sustainability awareness, interest, and engagement throughout the three semesters of the study. Some differences between engineering disciplines were visible, especially between sustainability-oriented engineering and the others. Most students who increased their sustainability awareness and interest were also likely to engage further with the topic. That engagement built up from individual engagement, to professional engagement and for some, into institutional and public sphere engagement. The findings are timely given the pressure faced by engineering education to incorporate sustainability issues. It provides avenues for educating engineering graduates who will display interest, awareness, and engagement with sustainability issues. It suggests institutional engagement as a potential avenue to explore for engineering educators.